Europe’s Continued Focus on Securitising African Migration Comes at a High Cost - Mbiyozo, Aimée-Noël (2023)
Since the 2015 migration ‘crisis’, Europe has increasingly applied a securitised approach to African migration: prioritising stemming flows and preventing irregular migrants from reaching Europe’s external borders. This approach has slowed arrivals but comes with severe costs. Africa has resisted many securitisation and externalisation measures because they do not serve African interests. Migration is viewed mostly positively across the continent. The African Union and Member States are working towards free movement and free trade to maximise development potential. Securitisation hinders this progress. Europe’s unrelenting focus on this issue is not commensurate with the actual number of African migrants who arrive irregularly in Europe. Impasses on this issue have already compromised more important agreements around trade, development, and security. Europe should carefully consider the impacts of its migration policies and weigh them against the real and prospective costs. Collaboration will succeed most in areas where African and European priorities converge.